Antifungal activity of yogurt-derived Lactobacillus spp. against Cryptococcus neoformans - SUHAIL JAWDAT FADHIL; ROAA MUHMMED YAHYA; MOHAMMED MAHMOOD HAMID (Society for Indonesian Biodiversity, 2025)
Abstract. Fadhil SJ, Yahya RM, Hamid MM. 2025. Antifungal activity of yogurt-derived Lactobacillus spp. against Cryptococcus neoformans. Biodiversitas 26: 3694-3700. As antifungal drug resistance continues to escalate, and Lactic Acid Bacteria (LAB) find increasing application as a probiotic in food systems and public health, this study explored the potential of LAB as a bio-protective agent. This study assessed the antifungal activity of (LAB) against fungal isolates of Cryptococcus neoformans, a significant fungal agent known for causing life-threatening infections, especially for immunocompromised patients. Sixteen LAB isolates were identified from ten sheep's milk yogurt samples, cultured on MRS agar, and incubated anaerobically at the optimum temperature for the isolation. Some probiotic characteristics, such as pH, bile salt, and phenol tolerance were confirmed. Ten of the isolates were bacilli others were cocci; most of them showed a high level of resistance to pH and high tolerance to 0.3% concentration of bile salt. All identified LAB isolates exhibited great resistance to 0.3% phenol. 25/100 (25%) isolates from the pigeon droppings sample were identified as C. neoformans; these isolates were biochemically identified after being cultured on Sabouraud Dextrose Agar (SDA) and Cryptococcus Differential Agar, exposed to standard antifungal agents, and then challenged with LAB prepared in three concentrations (104,106,108) on Mueller-Hinton agar overlaid with SDA. The antifungal activity of LAB against C. neoformans was investigated using the agar well diffusion method. The strains of C. neoformans exhibited 8%, and 4% resistance to fluconazole and itraconazole, respectively, whereas the isolates were all susceptible to amphotericin B and flucytosine. Among twenty C. neoformans strains challenged with LAB isolated from yogurt, 80% of them were susceptible by obvious inhibition at (108), whereas only five C. neoformans isolates were resistant to LAB. The observed antifungal activity of LAB against C. neoformans presents a promising opportunity for the development of bio-protective and therapeutic measures against C. neoformans and other fungi with related features.